Euthanasia Pasien Sekarat dalam Perspektif Hukum Islam: Euthanasia for Terminal Patients from the Perspective of Islamic Law - Maqsurah, Ainil; Muhammad Ikhsan; Afifah, Afifah (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
This research aims to find out the law committing an act of euthanasia for a dying patient. The type of research used is library research that is qualitative descriptive with methods of normative jurisprudence approach. The results of the study found that in the review of Islamic law active euthanasia in which a physician makes an active effort helps to accelerate the death of a patient, who is presumed and estimated to be unable to survive (death) even if at the request and consent of the patient or his family is explicitly prohibited, because such an act belongs to intentional murder. Nevertheless, there must be some other way of healing, for the purpose and purpose of a person's healing and life and death is ultimately in God's hand.